Spiritual Essence and Balance Development Model - Ade Manggala Hardianto; Yuli Novitasari (Eastasouth Institute, 2026)
Spiritual is the essence of human will and act according to the results of understanding the desired object. The purpose of the study is to test the influence of critical attitudes on the latent balance attitudes in humans. The research method uses a quantitative method that describes the initiative, understanding, and desires of individuals on objects. Data collection is the process of collecting data that indicates variations in question indicators that are distributed online. Population and sampling are a collection of primary data that have been determined by researchers on certain conditions, including having known BPR Syariah for a long time, respondents are at least 18 years old, have a minimum high school education (equivalent), and live around BPR Syariah. Data Analysis Technique is an Analysis Technique that has met the requirements to be worthy of being used as a population, model, and free from collinearity. The results of the study show that an individual's critical attitude can affect balance in oneself and their environment.